Template-assisted synthesis and characterization of passivated nickel nanoparticles - Gopalan, E. Veena; Malini, K. A.; Santhoshkumar, G.; Narayanan, T. N.; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Potential applications of nickel nanoparticles demand the synthesis of self-protected nickel nanoparticles by different synthesis techniques. A novel and simple technique for the synthesis of self-protected nickel nanoparticles is realized by the inter-matrix synthesis of nickel nanoparticles by cation exchange reduction in two types of resins. Two different polymer templates namely strongly acidic cation exchange resins and weakly acidic cation exchange resins provided with cation exchange sites which can anchor metal cations by the ion exchange process are used. The nickel ions which are held at the cation exchange sites by ion fixation can be subsequently reduced to metal nanoparticles by using sodium borohydride as the reducing agent. The composites are cycled repeating the loading reduction cycle involved in the synthesis procedure. X-Ray Diffraction, Scanning Electron Microscopy, Transmission Electron microscopy, Energy Dispersive Spectrum, and Inductively Coupled Plasma Analysis are effectively utilized to investigate the different structural characteristics of the nanocomposites. The hysteresis loop parameters namely saturation magnetization and coercivity are measured using Vibrating Sample Magnetometer. The thermomagnetization study is also conducted to evaluate the Curie temperature values of the composites. The effect of cycling on the structural and magnetic characteristics of the two composites are dealt in detail. A comparison between the different characteristics of the two nanocomposites is also provided.
Keywords: Nickel nanoparticles; Polymer-metal nanocomposites; Strongly acidic cation exchange resin; Stuctural and magnetic properties; Weakly acidic cation exchange resin